Safe distances for transforaminal posterior lumbar interbody fusion under one-hole split endoscopy: three-dimensional reconstruction measurement of 1-degree degenerative lumbar spondylolisthesis at the L4/5 segment - Changzhen Liu; Jiabin Ren; Zhaozhong Sun; Sa Li; Zhimeng Feng; Yuefei Li (Journal of Orthopaedic Surgery and Research)
Abstract Background One-hole split endoscopy (OSE) is a novel endoscopic technique that offers some advantages in spinal surgery. However, without a clear understanding of the safe zone for OSE, surgeons risk injuring nerve roots during the procedure. This study aimed to measure the safe distances among critical bone markers, the intervertebral space and nerve roots between 1-degree degenerative lumbar spondylolisthesis (DLS) and non-DLS at the L4/5 segment in patients via three-dimensional reconstruction and to compare the differences in relevant safety distances between the two groups. These findings provide a theoretical reference for the safe application of the OSE technique in transforaminal posterior lumbar interbody fusion (TPLIF). Methods The CT data of 56 patients were obtained, including 30 patients with 1-degree DLS at the L4/5 segment (DLS group) and 26 patients with non-DLS (non-DLS group). The bone markers were determined in a three-dimensional model. The relevant distances were as follows: (1) Vertical distance (VD): inferior articular process tip (IAPT) to the upper margin of the intervertebral space (VD1); superior articular process tip and the highest point of the mammillary process (HPMP) to the lower margin of the intervertebral space (VD2, VD3). (2) Horizontal distance (HD): the lateral boundary to the medial boundary at the upper margin of the intervertebral space (HD1) and at the lower margin of the intervertebral space (HD2); the medial margin of the articular surface in the coronal position of the superior articular process to the medial boundary at the lower margin of the intervertebral space (HD3); and the HPMP to the lateral boundary at the upper margin of the intervertebral space (HD4) and at the lower margin of the intervertebral space (HD5). Results In the DLS group and non-DLS group, the VD1 were (10.97 ± 2.15) mm and (11.32 ± 1.70) mm, the VD2 were (11.06 ± 1.75) mm and (10.96 ± 0.91) mm, the VD3 were (4.76 ± 1.54) mm and (5.01 ± 1.02) mm, the HD1 were (10.54 ± 1.49) mm and (10.97 ± 1.06) mm, the HD2 were (17.43 ± 2.01) mm and (17.32 ± 1.70) mm, and the HD3 were (2.21 ± 0.99) mm and (2.11 ± 1.33) mm. These measurement distances were not significantly different between the two groups. While HD4 (4.17 ± 1.41) mm in the DLS group was significantly greater than HD4 (3.29 ± 1.78) mm in the non-DLS group, HD5 (1.89 ± 0.93) mm in the DLS group was significantly lower than HD5 (2.63 ± 1.45) mm in the non-DLS group (P < 0.05). There was no significant difference between VD1 and VD2 in the DLS group. Conclusion Bone markers represent a novel positioning method for the treatment of 1-degree L4/5 segmental DLS under OSE, which will aid in avoiding nerve root injury and provide a reference for the safety of TPLIF. If HPMP is used as an auxiliary bone marker for decompression of the L4 exiting nerve root, HD4 was greater and HD5 was lower in the DLS group than in the non-DLS group during outwards fenestration and decompression. To improve safety, individualized imaging evaluation can be performed before the operation to select the appropriate grinding drill.